Model Diplomasi Kuno di Nusantara: Kasus Kesultanan Aceh dan Johor Abad XVI – XVII - Johan Wahyudi (Buletin Al-Turas, 2017)
AbstractNusantara is the land with various old tales. There is remaining some historical facts that is still urgent to discuss. One of past theme that is interesting is the relation of kingdoms and lands. Aceh Darussalam is one of the greatest kingdom in Sumatra and the strait of Malaka. Their existence had regarded as the guard, but for the other groups see it as threat. In some cases, that outlook can be changing, depending on the regional political context. The Kingdom of Johor becomes a one of political entity that is actively associated with Aceh. They need a strong colleague, in order to continue their development into estabilished kingdom. Their dark past, that is the fall of Malaka because Portuguese attack in 1511, is used for building a billateral cooperation with Aceh. Instead, the two kingdoms involved family relations. As we khow, marriage is the one of ancient diplomatic model in Middle Ages. During the wheel of time, the diplomatic boundery between Aceh and Johor is not always on the line. At the one day, Johor had known that Aceh had another goal behind his intentions. Aceh had planned that Johor is part of Aceh’s subordinate area. Therefore, Johor had decided Portuguese as his friend. This decision contraries to the vision of Aceh. Aceh had thougt that Portuguese is his rival. Aceh had showed his anger with several attacks to Johor. This Paper will explain the model of ancient diplomacies, in case of the relation of Aceh and Johor. Some kind of that such as the diplomacy in politic and intellectual sphere. ---AbstrakNusantara merupakan ranah yang kaya akan kisah masa lalu. Di dalamnya terendap beragam peristiwa yang masih aktual dibicarakan. Satu tema yang menarik adalah mengenai hubungan kenegerian antarkerajaan. Aceh Darussalam merupakan salah satu kerajaan besar di Sumatera dan perairan Malaka. Keberadaannya dianggap pengayom, namun bagi kelompok lain, ia diangap sebagai ancaman. Pada titik tertentu, pandangan ini bisa saja berubah-ubah, tergantung pada kondisi politik regional. Kesultanan Johor menjadi salah satu kesultanan yang aktif berhubungan dengan Aceh Darussalam. Johor membutuhkan rekanan yang tangguh, agar bisa terus berkembang menjadi kerajaan yang mapan. Masa lalu yang kelam, yakni dikuasainya Malaka oleh Portugis pada 1511, membulatkan tekad Johor untuk beriringan dengan Aceh dalam kerjasama bilateral. Malah, kedua kerajaan terikat oleh hubungan kekerabatan. Hal ini karena beberapa pangeran dan putri Johor menikah dengan pangeran dan putri dari Aceh. Seperti diketahui, pernikahan merupakan bentuk diplomasi kuno di Abad Pertengahan. Dalam perjalanannya, diplomasi yang dijalin Aceh dan Johor tidaklah berjalan mulus. Pada satu keadaan, Johor menyadari bahwa Aceh mempunyai motif lain, yakni ingin menjadikan Johor bagian dari daerah pengaruhnya. Oleh sebab itu, Johor memutuskan menjalin hubungan dengan Portugis, agar bisa lepas dari bayang-bayang Aceh. Aceh yang memang menjadikan Portugis sebagai rivalnya, marah dengan kebijakan Johor. Sejak itu di beberapa fase hubungan Aceh dan Johor terlibat peperangan. Tulisan ini akan mengangkat model dua diplomasi kuno seperti yang tersaji dalam kasus kerajaan Aceh dan Johor. Beberapa yang bisa disebutkan adalah diplomasi politik dan intelektual.  DOI: 10.15408/al-turas.v23i1.4800